Teori Kesadaran dan Psikoanalisis Sigmund Freud terhadap Karya Sastra Realisme Sosialis - Arini Rachma Ramadhani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
A person's psychology is greatly influenced by various life problems such as the emergence of inner conflicts due to environmental influences, association and even economic factors. Events like this are also often told in literary works played by important historical figures. This Research Discusses Sigmund Freud's Theory of Consciousness and Psychoanalysis on the Development of Human Personality. Analyzing Pramoedya Ananta Toer's novel and Socialist Realism Literature by providing a clear picture of the thoughts and aesthetics of socialist realism using a qualitative descriptive approach. In all his writings and literary works, Pramoedya always offers and fights for socialist realism against other isms. Even in the novel Socialist Realism Literature, he fights for his ideology against feudalism and authoritarianism.